Multi-layer Barrier Coating Technology Using Nano- fibrillated Cellulose and a Hydrophobic Coating Agent - Hae Min Jo; Do Hoon Kim; Soo Hyun Lee; Ji Young Lee (BioResources, 2022)
A multi-layer barrier coating technology was developed using nano-fibrillated cellulose (NFC) alongside a hydrophobic, paraffin-free biowax for manufacturing an eco-friendly functional packaging paper. Anionic NFC was prepared by isolating hardwood-bleached kraft pulp (Hw-BKP) using a micro-grinder, and cationic NFC was prepared by the quaternization reaction of the anionic NFC. Thereafter, a three-layer barrier-coated paper was manufactured using cationic and anionic NFCs and biowax. The air permeability and water vapor transmission rate (WVTR) of the three-layer barrier-coated paper were measured, and its coverage and coating layer structure were observed by scanning electron microscopy (SEM). The air permeability of the three-layer barrier-coated paper was more than 15,000 s and those WVTR was 67.1 g/m2/day. Its coverage and surface were considerably uniform and smooth. Thick and effective barrier coating layers were formed as indicated by SEM images. Therefore, it was concluded that a multi-layer barrier-coated paper with considerably high barrier properties could be produced using cationic and anionic NFCs with high gas barrier properties and biowax with high moisture barrier properties. Further, the structure could be used as a functional packaging paper with high barrier properties.